Analisis Faktor - Faktor Yang Mempengaruhi NilaiPerusahaan Pada Perusahaan Sektor KeuanganYang Terdaftar Di Bursa Efek Indonesia - Kusumastuti, Dewi; , Muhammad Sholahuddin, S.E, Msi (2017)
The purpose of this study was to analyze the effect of good corporate governanace (GCG), and the financial performance of the company's value. The research object is the entire financial sector companies go public, amounting to 5 sub-sectors, and there are 78 companies. However, based on the completeness of data then only 32 companies were sampled with the observation period in 2015. The independent variables were the company's performance (return on assets, return on equity, Operating Profit Margin, Net Profit Margin), and Good Corporate Governanace (Board of Commissioners and the Audit Committee ), while the enterprise value of the dependent variable (Price Book value). The data analysis used multiple linear regression analysis. The results of this study indicate that ROA, ROE, NPM and KA have a significant influence on the value of the company, while the OPM, and GCG does not have a significant influence on the value of the company.